Carotid artery plaque uptake of 11C-PK11195 inversely correlates with circulating monocytes and classical CD14++CD16− monocytes expressing HLA-DR. (December 2018) - Ammirati, Enrico; Moroni, Francesco; Magnoni, Marco; Busnardo, Elena; Di Terlizzi, Simona; Villa, Chiara; Sizzano, Federico; Scotti, Isabella; Palini, Alessio; Presotto, Luca; Bettinardi, Valentino; Spagnolo, Pietro; et al.
Abstract: Background: We explored the relation between blood concentrations of monocyte/lymphocyte subsets and carotid artery plaque macrophage content, measured by positron emission tomography (PET) with 11 C-PK11195. Methods and results: In 9 patients with carotid plaques we performed 11 C-PK11195-PET/computed tomography angiography imaging and measurement of absolute concentrations and frequencies of circulating monocytes and T-cell subsets. Plaque standardized uptake value (SUV) for 11 C-PK11195 was negatively correlated with concentrations of total monocytes (r = −0.58, p = 0.05) and CD14 ++ CD16 − HLA-DR + classical subset (r = −0.82, p = 0.005). These correlations hold true also in relation to plaque target to background ratio. No correlation was observed between plaque SUV and CD3 + T lymphocytes, CD4 + T lymphocytes nor with activated CD3 + CD4 + T cells expressing HLA-DR. Conclusions: We first demonstrated a reduction in the absolute concentration of monocytes and particularly in classical monocytes expressing HLA-DR in the presence of an increased uptake of 11 C-PK11195 in carotid plaques. The present work, despite being a pilot study comprising only a small number of subjects provides new insights in the search for specific cellular biomarkers with potential diagnostic and prognostic value in patients with a known carotid plaque.